Antibiotics Misuse - Ibrahim, Rahaff; Najem, Abbas; Reda, Nesma (Faculty of pharmacy, 2019)
Fleming (1928) began to sort through Petri dishes containing colonies of Staphylococcus, bacteria that cause boils, sore throats and abscesses. He noticed something unusual on one dish. It was dotted with colonies, except for one area where a blob of mold was growing. The zone immediately around the mold—later identified as a rare strain of Penicillium notatum—was clear, as if the mold had secreted something that inhibited bacterial growth, which is now known as antibiotics. Antibiotic is a drug used to treat bacterial infections. It has no effect on viral infections. Originally, an antibiotic was a substance produced by one microorganism that selectively inhibits the growth of another. Synthetic antibiotics, usually chemically related to natural antibiotics, have since been produced that accomplish comparable tasks. But some medications that used to be standard treatments for bacterial infections are now less effective or don't work at all because of misuse.